The Value of Discretionary Accruals Computed Using both National and International Standards - Florin Dobre; Laura Brad; Radu Ciobanu (Journal of Accounting and Management Information Systems (JAMIS), 2015)
The present research provide information about the value of discretionary accruals considering the fact that a switch from Romanian Accounting Standards to International Financial Reporting Standards was compulsory, from 2012, for the entities that have securities admitted on trading. The value of discretionary accruals has been estimated using two methods, but either of them has provided pertinent information about a difference in the value of discretionary accruals. A comparison between the mean, the median and the variance of discretionary accruals computed under the two accounting regimes has been conducted, but not a statistically significant difference could be detected. Moreover, no influence of specific factors could be observed on the value of discretionary accrual.
Keywords: M41; M21; 650; discretionary accruals; IFRS; transition period; Romania